Pre‐oxygenation and apnoea in pregnancy: changes during labour and with obstetric morbidity in a computational simulation - McClelland, S. H.; Bogod, D. G.; Hardman, J. G. (Anaesthesia, 2009)
Summary Using the Nottingham Physiology Simulator, we investigated the effects on pre‐oxygenation and apnoea during rapid sequence induction of labour, obesity, sepsis, pre‐eclampsia, maternal haemorrhage and multiple pregnancy in term pregnancy. Pre‐oxygenation with 100% oxygen was followed by simulated rapid sequence induction when end‐tidal nitrogen tension was less than 1 kPa, and apnoea. Labour, morbid obesity and sepsis accelerated pre‐oxygenation and de‐oxygenation during apnoea. Fastest pre‐oxygenation was in labour, with 95% of the maximum change in expired oxygen tension occurring in 47 s, compared to 97 s in a standard pregnant subject. The labouring subject with a body mass index of 50 kg.m−2 demonstrated the fastest desaturation, the time taken to fall to an arterial saturation < 90% being 98 s, compared to 292 s in a standard pregnant subject. Pre‐eclampsia prolonged pre‐oxygenation and tolerance to apnoea. Maternal haemorrhage and multiple pregnancy had minor effects. Our results inform the risk‐benefit comparison of the anaesthetic options for Caesarean section.